The Concept of Land Ownership in Islam and Poverty Alleviation in Pakistan (The Pakistan Development Review, 2000)
Land ownership—in its ethico-legal and historical manifestations, reflects the importance of being a politico-economic institution. In the process of its development, it includes various heterogeneous elements of different systems of ownership. With the growth of the Ummah, the principles of laws of ownership represent and embody the relations, rights and duties to form the general law of obligations at the state as well as individual level. This is the case of economic and legal theory, regarding the ownership of land with implicative infrastructure to build social welfare institutions of Islam. It is generally and basically have been ordained that according to the teachings of Islam, Real ownership belongs to Allah Almighty. Man being the vicegerent holds property in trust for which he is accountable to him in accordance with the clearly laid down economic philosophy of Islam. Ownership of man is a concept alien to Islam as it belongs to Allah Almighty only.